Stagnation point flow over a stretching/shrinking sheet in a carbon nanotubes with suction/injection effects - Norzawary, Nur Hazirah Adilla; Bachok, Norfifah; Md. Ali, Fadzilah (The International Society for Science & Religion (I S S R), 2020)
This research is to explore the stagnation point flow problem in carbon nanotubes (CNTs) with suction/injection impacts over a stretching/shrinking sheet. Nonlinear ordinary differential equations systems are transformed from the governing partial differential equations by applying similarity transformation, thus resolved numerically using a bvp4c solver in MATLAB. Two types of CNTs are used which are SWCNTs (singlewalled) and MWCNTs (multi-walled) and water as the base fluids. Influence of the velocity, temperature, skin friction and Nusselt numbers are studied and displayed in the graphs form. It is concluded that the suction effect could widen the range of solutions exist and the effect of injection acted on the contrary. Also, the solutions are dual for shrinking sheet while unique for stretching sheet.